2021
DOI: 10.3390/bs11030039
|View full text |Cite
|
Sign up to set email alerts
|

How Downward and Upward Comparisons on Facebook Influence Grandiose and Vulnerable Narcissists’ Self-Esteem—A Priming Study

Abstract: Past research showed that social networking sites represent perfect platforms to satisfy narcissistic needs. The present study aimed to investigate how grandiose (GN) and vulnerable narcissism (VN) as well as social comparisons are associated with Facebook activity, which was measured with a self-report on three activity dimensions: Acting, Impressing, and Watching. In addition, the state self-esteem (SSE) was measured with respect to performance, social behavior, and appearance. One hundred and ten participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…A recent meta-analysis by Casale and Banchi (2020) found that studies that have investigated vulnerable narcissism and problematic social media use reported a significant moderate positive association [26][27][28]. Recent studies also suggested that vulnerable narcissism, but not grandiose narcissism, is the primary determinant of Facebook use [29,30]. Furthermore, a study comparing vulnerable and grandiose narcissists found significantly higher levels of problematic internet use and a stronger preference for online social interactions compared to grandiose narcissists [18].…”
Section: Narcissism and Social Media Usementioning
confidence: 99%
“…A recent meta-analysis by Casale and Banchi (2020) found that studies that have investigated vulnerable narcissism and problematic social media use reported a significant moderate positive association [26][27][28]. Recent studies also suggested that vulnerable narcissism, but not grandiose narcissism, is the primary determinant of Facebook use [29,30]. Furthermore, a study comparing vulnerable and grandiose narcissists found significantly higher levels of problematic internet use and a stronger preference for online social interactions compared to grandiose narcissists [18].…”
Section: Narcissism and Social Media Usementioning
confidence: 99%